Ethics-Based Leadership in Managing Information Security and Data Privacy - Zuhri Halim; Ngurah Pandji Mertha Agung Durya; Kraugusteeliana Kraugusteeliana; Suherlan Suherlan; Ayu Latifah Alfisyahrin (Politeknik Ganesha Medan, 2023)
In the advancing digital age, technological transformation has created endless opportunities for efficiency, innovation and connectivity. However, behind these advancements lie significant challenges related to information security and data privacy. Adverse data breaches and cyber-attacks have reminded us of the vulnerabilities inherent in today's digital environment. Therefore, protecting information security and data privacy has become a top priority for organisations around the world. This research aims to explore how ethical leaders can influence decision-making and practices related to information security and data privacy. This research is a literature review that adopts a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results arrive at a statement that ethical leaders ensure that technical aspects and ethical values go hand in hand in making decisions related to information security and data privacy. Through ethics-based leadership, organisations are able to build a culture that cares about data privacy, create a secure and transparent environment for customers and users, and comply with increasingly stringent regulations. The trust of customers and business partners built through ethical practices in information and data management will be a competitive advantage for organisations in the ever-changing digital age.